Targeting the psychosocial and functional fitness challenges of older adults with hearing loss: a participatory approach to adaptation of the walk and talk for your life program. (3rd July 2018) - Jutras, Marc; Lambert, Justin; Hwang, Jiyoung; Wang, Lisa; Simon, Shane; Del Medico, Talia; Mick, Paul; Miller, Harry; Kurtz, Donna; Murphy, Mary-Ann; Jones, Charlotte Ann
Abstract: Objective : Explore the acceptability of a socialisation, health education and falls prevention programme (Walk and Talk for Your Life: WTL) as an adjunct to group auditory rehabilitation (GAR) and how it might be adapted for older adults with hearing loss (HL). Design : Content theme analysis (CTA) of guided interviews explored the experience of HL, the acceptability of a WTL programme and suggestions on how to adapt the WTL programme to better suit the needs of older adults with HL. Study sample : Twenty-eight (20 women, 8 men) adults (>55 years of age) with HL were interviewed. Seventeen had participated in past WTL programmes and eleven were sampled from the community. Results : Interviewees reported difficulty socialising and a tendency to withdraw from social interactions. Addition of GAR to a WTL programme was found to be highly acceptable. Interviewees suggested that to best suit their needs, sessions should take place in a location with optimal acoustics; include small groups integrating hearing-impaired and hearing-intact participants; include appropriate speaking ground rules; and include an option for partner involvement. Conclusions : The adapted WTL programme provides a holistic and unique approach to the treatment of HL that has the potential to positively impact the hearing-impaired elderly.